Three essays on the macroeconomics of human capital and growth - Palamuleni, Mercy Laita (Kansas State University, 2014)
This dissertation encompasses three essays on the macroeconomics of human capital and economic growth. Below are the individual abstracts for each essay. Essay 1: Does Public Education Spending Increase Human Capital? I investigate the effect of public education spending on the quality of human capital as measured by international student test scores in science and mathematics, conditional on the efficiency of a country's governance. Combining World Bank country level data on government efficiency with rich micro data from the OECD PISA-2009, I estimate a human capital production function from student level data. Prior work suggests that public education expenditures are inconsequential for student achievement. I illustrate that public education spending matters for student test scores when one uses student level data instead of aggregate country level data. These results are robust to controlling for governance measures such as corruption control and regulatory quality. An implication is that less efficient government does not preclude improving test scores through education spending. Essay 2: Inequality of Opportunity in Education: International Evidence from PISA. I provide lower-bound estimates of inequality of opportunity in education (IEO) using micro-data from the Programme for International Student Assessment (PISA). The measure represents variation in student mathematics test scores which can be explained by predetermined circumstances (including parental education, gender, and additional community variables). I explore the heterogeneity of the measure at the top and bottom of the test score distribution, and demonstrate that IEO accounts for 10 percent of the variation in test scores for students at the top and bottom of the test score distribution. Using this inequality measure I establish three main conclusions. (1) IEO decreases overall in response to an increase in preprimary enrollment rates. An implication here is that improvements in early childhood education might mitigate the effects of IEO factors for some students. (2) IEO increases in a manner which relates to overall inequality. This indicates the possibility of a more general persistence to inequality factors. An implication is that equity-based education policies can be a key tool for reducing income inequality. (3) There is evidence of an equity-efficiency tradeoff in education. An implication here is that public education policies aimed at reducing IEO might hinder overall education efficiency, in that it decreases academic achievement for some groups of students. Essay 3: Public Education Spending and Economic Growth: The Role of Governance. Although the theoretical literature often connects public education spending to growth, individual empirical findings sometimes conflict. In this paper I propose that inefficiencies in public education spending might explain these inconsistencies. Using a dataset from both developed and developing countries observed over the period of 1995 to 2010, I demonstrate that the efficiency of public education spending on growth depends on a country's level and quality of governance. I also find evidence that increasing educational spending is associated with higher economic growth only in countries that are less corrupt. These findings have important implications for the formation of effective education policies in developing countries. They illustrate that efficient public education spending augments economic growth in a way that increased spending alone does not match.
Keywords: Macroeconomics; Economic growth; Labor economics; Human capital; Inequality in education; Public spending; Economics (0501)